Tourism and growth in European countries: an application of likelihood-based panel cointegration - de Sousa-Vale, S.; de Mello-Sampayo, F. (International Conference of the ERCIM WG on COMPUTING & STATISTICS (ERCIM'10), 2010)
The tourism and economic growth relationship is investigated for a panel of European countries over the period 1988-2010. The results reveal that the variables contain a panel unit root and they cointegrate in a panel perspective. The findings show that tourism enhance economic growth for some countries in the sample. The paper is organized as follows: first, we present a simple theoretical model, then we describe the sources of data and report our panel test results for unit roots, cointegration and ranks. Finally, we discuss the long run relationship equilibrium taking into account the cross dependence within the panel to conclude that tourism is important for economic growth but with a smaller magnitude than expected.